Diagnóstico sectorial de la actividad de venta al por menor de electrodomésticos en el cantón Loja - Ortiz Chimbo, Kasandra Anabel (2023)
Sectorial diagnosis is currently highly relevant at the global, regional, and local scales because it focuses on analyzing the variables that allow measuring and comparing the performance of organizations in the sector in which they operate, making factual and informed decisions, and improving their performance, which translates into sustainability. This research work aims to carry out a sectorial diagnosis of the retail sales activity of household appliances in Loja canton. A qualitative methodology was used to analyze the sector, and a quantitative approach was used to determine statistics and averages for the industry. The main results indicate that the sector has 55 companies in the canton of the activity with ISIC code G4759.05, in the characterization, entry barriers are identified, such as experience investment amounts, among others; and customer segmentation that considers geographic, demographic, and behavioral variables; the main critical success factors to improve the operation of the companies lie in the control of internal processes, advertising and promotions, geographic location and efforts in learning and growth of human talent, as well as the leading financial averages such as working capital is $6 787.09; its current ratio is $4.41 to cover its obligations, and an average of 54% of its assets are financed by its liabilities. As a non-financial indicator, it has an average monthly sale of $18 470,09 with an average of 94 clients per month and an investment of approximately $61 in advertising, representing an effectiveness of $1 007,18. Finally, it was concluded that 55 companies exist with 127,987 families as potential clients, of whom 34 provided information; in addition, organizations should consider the barriers to entry, critical success factors, and the averages presented to evaluate their performance.